Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Pregnancy in Sub-Saharan Africa: A 6-Country Retrospective Cohort Analysis. (8th June 2022) - Nachega, Jean B; Sam-Agudu, Nadia A; Machekano, Rhoderick N; Rosenthal, Philip J; Schell, Sonja; de Waard, Liesl; Bekker, Adrie; Gachuno, Onesmus W; Kinuthia, John; Mwongeli, Nancy; Budhram, Samantha; Vannevel, Valerie; et al.
Abstract: Background: Few data are available on COVID-19 outcomes among pregnant women in sub-Saharan Africa (SSA), where high-risk comorbidities are prevalent. We investigated the impact of pregnancy on SARS-CoV-2 infection and of SARS-CoV-2 infection on pregnancy to generate evidence for health policy and clinical practice. Methods: We conducted a 6-country retrospective cohort study among hospitalized women of childbearing age between 1 March 2020 and 31 March 2021. Exposures were (1) pregnancy and (2) a positive SARS-CoV-2 RT-PCR test. The primary outcome for both analyses was intensive care unit (ICU) admission. Secondary outcomes included supplemental oxygen requirement, mechanical ventilation, adverse birth outcomes, and in-hospital mortality. We used log-binomial regression to estimate the effect between pregnancy and SARS-CoV-2 infection. Factors associated with mortality were evaluated using competing-risk proportional subdistribution hazards models. Results: Our analyses included 1315 hospitalized women: 510 pregnant women with SARS-CoV-2, 403 nonpregnant women with SARS-CoV-2, and 402 pregnant women without SARS-CoV-2 infection. Among women with SARS-CoV-2 infection, pregnancy was associated with increased risk for ICU admission (adjusted risk ratio [aRR]: 2.38; 95% CI: 1.42–4.01), oxygen supplementation (aRR: 1.86; 95% CI: 1.44–2.42), and hazard of in-hospital death (adjusted sub-hazard ratio [aSHR]: 2.00; 95% CI: 1.08–3.70). Among pregnant women, SARS-CoV-2 infection increased the risk of ICU admission (aRR: 2.0; 95% CI: 1.20–3.35), oxygen supplementation (aRR: 1.57; 95% CI: 1.17–2.11), and hazard of in-hospital death (aSHR: 5.03; 95% CI: 1.79–14.13). Conclusions: Among hospitalized women in SSA, both SARS-CoV-2 infection and pregnancy independently increased risks of ICU admission, oxygen supplementation, and death. These data support international recommendations to prioritize COVID-19 vaccination among pregnant women. Abstract : In hospitalized African women, both SARS-CoV-2 infection and pregnancy independently increased risks of morbidity and mortality. In addition, among pregnant and nonpregnant women with SARS-CoV-2 infection, HIV, prior tuberculosis, sickle cell anemia, and nongestational diabetes increased risk of ICU admission.